Adaptation, Poverty and Well-Being: Some Issues and Observations with Special Reference to the Capability Approach and Development Studies. - Clark, D (GPRG, 2007)
The idea that people adapt to poverty and deprivation by suppressing their wants, hopes and aspirations has gained a lot of currency in development ethics. While the ‘adaptation problem’ is often cited as one of the primary arguments for abandoning utility based concepts of well-being in favour of the capability approach, it also has serious implications for the capability approach and development studies generally. These implications are not normally discussed or acknowledged in the well-being and development literature. Fortunately for development studies, the available evidence suggests that adaptation is not ubiquitous. Moreover, where adaptation occurs, there is some evidence to suggest that it takes a different – and far less damaging – form than the type discussed in work on human well-being and development.programme of the ESRC Global Poverty Research Group